ANALISIS EKSPOR BATUBARA INDONESIA KE NEGARA TUJUAN UTAMA (INDIA, TIONGKOK, JEPANG, KOREA SELATAN, MALAYSIA) - Yafet Setiadi Simanjuntak; Rahma Nurjanah; Faradina Zevaya (Jurnal Riset Multidisiplin Edukasi, 2026)
This study examines the development of Indonesian coal exports and the influence of destination country GDP, the benchmark coal price, the exchange rate, and the population of destination countries on the volume of Indonesian coal exports to major destination countries, namely India, China, Japan, South Korea, and Malaysia, from 2017 to 2024. This study uses secondary data obtained from official publications by the Central Statistics Agency (BPS), the Ministry of Energy and Mineral Resources (ESDM), and the World Bank. The analytical method used is panel data regression with a double logarithmic model using the Common Effect Model approach, processed using EViews 12 software. The panel data regression results indicate that overall Indonesian coal export volume and the research variables fluctuated during the 2017-2024 period, with different trends for each variable. The regression estimation results using this approach indicate that destination country GDP and the exchange rate have a negative and significant effect on Indonesian coal exports. Conversely, destination country population has a positive and significant effect on Indonesian coal exports. Meanwhile, the benchmark coal price has no significant effect on Indonesian coal exports.